Inflation targeting and real exchange rates in emerging markets - Joshua Aizenman; Michael Hutchison; Ilan Noy (University of California, Economics Department, 2008)
We examine the inflation targeting (IT) experiences of emerging market economies, focusing especially on the roles of the real exchange rate and the distinction between commodity and non-commodity exporting nations. In the context of a simple empirical model, estimated with panel data for 17 emerging markets using both IT and non-IT observations, we find a significant and stable response running from inflation to policy interest rates in emerging markets that are following publically announced IT policies. By contrast, central banks respond much less to inflation in non-IT regimes. IT emerging markets follow a 'mixed IT strategy' whereby both inflation and real exchange rates are important determinants of policy interest rates. The response to real exchange rates is much stronger in non-IT countries, however, suggesting that policymakers are more constrained in the IT regime-they are attempting to simultaneously target both inflation and real exchange rates and these objectives are not always consistent. We also find that the response to real exchange rates is strongest in those countries following IT policies that are relatively intensive in exporting basic commodities. We present a simple model that explains this empirical result.
Keywords: E52; E58; F3; 330; inflation targeting; real exchange rate; commodity exporters; emerging markets; Inflation Targeting; Wechselkurs; Kaufkraftparität; Export; Aufstrebende Märkte; Schwellenländer